Pariwisata dan Praktik Ilegal “Jaringan Tiongkok” di Bali - Zefanya S.D.I Picaulima; Hermini Susiatiningsih; Fendy Eko Wahyudi (Journal of International Relations, 2022)
The increase in Bali tourism can be seen through the suffering of Chinese tourists in Bali in 2017. However, behind the domination of Chinese tourists in Bali, unknowingly there are illegal practices carried out by the "Chinese Network" in Bali, which has caused the image of Bali tourism to become unhealthy and bad. Therefore this research will discuss how behind the domination of Chinese tourists in Bali there is a Chinese network that moves illegally in detail about the Chinese network, then how the policies of the Government of Indonesia and the Provincial Government of Bali respond to this issue. This study uses the concept of the Chinese School to see the ideological values applied to Chinese identity, then the concept of Guanxi which is one of the keys to China's success in doing business. This study uses a descriptive qualitative approach with sources obtained through literature studies and primary sources in the form of documentation. The findings in this study are that the China Network consists of Chinese Entrepreneurs and Travel Agents. These two actors work together to carry out their activities in Bali by attracting Chinese tourists and selling Chinese-produced goods. The impact of this illegal activity gives a bad view of the image of Bali tourism and affects the Indonesian economy, especially Bali.